Descriptive Analysis of Student Learning Outcomes in Online and Offline Biology Learning - Shellya Puti Sudesty; Rahmawati Darussyamsu (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
This study aims to describe and analyze student learning outcomes in online and offline biology learning at SMAN 1 Padang, West Sumatra. This type of research is descriptive research with the sampling technique used being total sampling. The research sample was 555 students of class X MIPA in 2019 and 2020. The data collection technique in this study used documentation and interview techniques. The data of this research used documents of student learning outcomes and interviews with one of the biology subject teachers. The results of this study indicate that: (1) the percentage of students' complete learning outcomes in offline biology learning is 87% with effective qualifications. (2) the percentage of complete learning outcomes of students in online biology learning is 65% with quite effective qualifications. (3) the percentage of learning completeness in offline biology learning has reached a predetermined percentage, while online biology learning has not yet reached the predetermined percentage of learning completeness. Based on the results of data analysis, it can be concluded that in SMA Negeri 1 Padang offline biology learning is more effective than online biology learning